Perbandingan Performasi Metode Johnson dengan Heuristik Multi Tujuan Ditinjau dari Makespan Total Flow Time dan Iddle Time - Annisa Kesy Garside (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
This researchtd es to implementa methodo f rnachines chedulingfo r flow shopc alledMulti ObjectiveH euristicT. o makee asiera pplicationin attainingjo b sequencteh atm achinem ustdo alongw ith makespavna lue,l otal flow time, andi dle time,t hen a softwareis made Next, wemakea iomparisono f machines chedulingre sultp erformancbee tweenM ulti objectiveH euristicMethoda ndl ohnsonM ethodi f viewedf iom makespavna lue,t otalf low time,a ndi dlet ime. Fromthe resulto f researchc oncludedth at heuristic with multi objectivesm ethods howst he solutionsflow timet otalf ewert hanJ ohnsonm ethod